The Moment of Truth: A Key to Successful Services Marketing - Hultman, Jens (INTI Publishing House Sdn Bhd, 2005)
This paper highlights the importance of the moment of truth in services marketing. The moment of truth is argued to be a notion that bridges the concept of the service encounter with the concept of the expected and experienced quality. This paper is outlined as follows: First, the service encounter is framed and the paper then addresses the concepts of service quality and expectations. When addressing expectations, specific attention is given to the zone of tolerance, a concept outlining the boundaries within which the expectations are seen as either met or not met. Second, implications for managers in service markets regarding the moment of truth arc outlined. The paper concludes by raising current issues such as outsourcing, quality control and over performance in service production.